Comparing the "Interests of Justice": What the International Criminal Court Can Learn from New York Law - Linda M. Keller (Washington University Global Studies Law Review, 2013)
This article addresses the debate over whether the Prosecutor of the International Criminal Court should adopt ex ante guidelines for prosecutorial discretion in order to increase transparency and legitimacy. It focuses on one of the most ambiguous provisions of the Rome Statute: allowing the Prosecutor to decline to prosecute in the “interests of justice.” Specifically, this article will examine the experience of New York in operationalizing a domestic statutory analogue to the Rome Statute provision: dismissal of cases “in furtherance of justice.” An analysis of New York law yields three core lessons that carry over to the international sphere despite differences in the systems. First, a requirement of a written rationale regarding the exercise of discretion does not necessarily yield thorough or convincing explanations. This undermines arguments that the legitimacy of the International Criminal Court will be enhanced by public explanations of prosecutorial discretion. Second, such explanations may backfire when the balancing of nebulous factors leads to apparently inconsistent or arbitrary reasoning and results, which may undercut the credibility of the decision-maker. Finally, the lack of a guiding theory to drive the interpretation of ambiguous criteria can lead to more confusion than clarity when there is no agreement on the theoretical justifications for prosecution, as seen in both the domestic and international systems. The experience of New York, therefore, supports skepticism of the efficacy of ex ante criteria for the exercise of discretion, particularly for complex decisions regarding the interests of justice. If such criteria are nonetheless adopted, the New York experience offers suggestions on crafting a more effective approach.
Keywords: International Criminal Court; New York law; prosecution; prosecutorial discretion; Rome Statute; comparative law